Complete neural stem cell (NSC) neuronal differentiation requires a branched chain amino acids-induced persistent metabolic shift towards energy metabolism. (August 2020) - Bifari, Francesco; Dolci, Sissi; Bottani, Emanuela; Pino, Annachiara; Di Chio, Marzia; Zorzin, Stefania; Ragni, Maurizio; Zamfir, Raluca Georgiana; Brunetti, Dario; Bardelli, Donatella; Delfino, Pietro; Cattaneo, Maria Grazia; et al.
Graphical abstract: Abstract: Neural stem cell (NSC) neuronal differentiation requires a metabolic shift towards oxidative phosphorylation. We now show that a branched-chain amino acids-driven, persistent metabolic shift toward energy metabolism is required for full neuronal maturation. We increased energy metabolism of differentiating neurons derived both from murine NSCs and human induced pluripotent stem cells (iPSCs) by supplementing the cell culture medium with a mixture composed of branched-chain amino acids, essential amino acids, TCA cycle precursors and co-factors. We found that treated differentiating neuronal cells with enhanced energy metabolism increased: i) total dendritic length; ii) the mean number of branches and iii) the number and maturation of the dendritic spines. Furthermore, neuronal spines in treated neurons appeared more stable with stubby and mushroom phenotype and with increased expression of molecules involved in synapse formation. Treated neurons modified their mitochondrial dynamics increasing the mitochondrial fusion and, consistently with the increase of cellular ATP content, they activated cellular mTORC1 dependent p70S6 K1 anabolism. Global transcriptomic analysis further revealed that treated neurons induce Nrf2 mediated gene expression. This was correlated with a functional increase in the Reactive Oxygen Species (ROS) scavenging mechanisms. In conclusion, persistent branched-chain amino acids-driven metabolic shift toward energy metabolism enhanced neuronal differentiation and antioxidant defences. These findings offer new opportunities to pharmacologically modulate NSC neuronal differentiation and to develop effective strategies for treating neurodegenerative diseases.